2005
DOI: 10.1086/444462
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan Does Not Precede Major Signs on a Pulmonary Computerized Tomographic Scan Suggestive of Invasive Aspergillosis in Patients with Hematological Malignancies

Abstract: We show that detection of GM by EIA does not precede detection of major lesions by pulmonary CT. In the clinical setting, the decision to administer mold-active treatment should based on detection of new pulmonary infiltrates on CT performed early during infection, rather than on results of EIA for detection of GM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 41 publications
(57 reference statements)
0
70
1
4
Order By: Relevance
“…To obtain such results, blood samples must be taken at least twice per week and the optical density index set to 1. However, these results were not confirmed by others [90][91][92], and some authors even reported sensitivity as low as 29.4% [93]. In a multicentre study, sensitivity and specificity were found to be 50 and 97%, respectively, and only one-third of the patients had a positive antigen response before IPA diagnosis on CT scan [74].…”
Section: Serologymentioning
confidence: 72%
“…To obtain such results, blood samples must be taken at least twice per week and the optical density index set to 1. However, these results were not confirmed by others [90][91][92], and some authors even reported sensitivity as low as 29.4% [93]. In a multicentre study, sensitivity and specificity were found to be 50 and 97%, respectively, and only one-third of the patients had a positive antigen response before IPA diagnosis on CT scan [74].…”
Section: Serologymentioning
confidence: 72%
“…All centers agreed to complete an No. developing grades II-IV aGVHD (% CumInc, 95% CI) 53 (36,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) 17 (26, 14-38) 36 (44, 32-56) .03…”
Section: Methodsmentioning
confidence: 99%
“…These approaches are limited by the insensitivity of cultures and the invasiveness of transbronchial biopsies. Presumptive diagnoses based on the evolution of lesions detected by thoracic computed tomography (CT) scanning facilitate the institution of therapy in the absence of culture or biopsy results (2,3,12,24), but this strategy is limited by low sensitivity and a lack of specificity for IPA compared to other infectious processes (25). Moreover, classic halo and air crescent signs are well described among neutropenic hosts but are less common in solid-organ transplant recipients (9,21).…”
mentioning
confidence: 99%